Digital Banking Support to Small Businesses amid COVID-19 : Evidence from China - Sun, Tao (International Monetary Fund, 2021)
This note analyzes the economic impact of digital lending to micro and small sized enterprises (MSEs) in China during the coronavirus disease (COVID-19) pandemic. A preliminary analysis of a large pool of MSEs served by a digital bank indicates that digital banks were able to remotely evaluate borrowers and sustain lending during the pandemic, thereby facilitating the business continuity, sales growth, and financial inclusiveness of MSEs. In the global context, a policy framework-leveraging the advantages of digital banks and empowering digital banks, while guarding against possible financial stability risks-would further support small businesses during and after the COVID-19 pandemic.